FEATURES OF ENVIRONMENTAL DISCOURSE IN THE INFORMATION AGE - Skyba, Oksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The article states that at the current stage of society's development, the aggravation of the ecological situation puts the problem of nature conservation as one of the first places of global problems of mankind. And the formation of modern ecological discourse is closely related to the formation of ecological culture and the search for new moral and ethical value orientations. The aim and tasks are studies of the peculiarities of the functioning of ecological discourse in the information age and its influence on the functioning of the ecological sphere of knowledge. Research methods. The theoretical and methodological basis of the study of the modern ecological discourse is the comparative and axiological, systemic, and complex approaches. Research results. Human ecology as a science arises at the crossroad of many sciences including the ideas of many researchers and continues to interact today with other sciences (philosophy, biology, geography, medicine, etc.). In the conditions of the modern global ecological crisis, the main attention should be directed to man, because the former is a result of the technogenic activity that humanity has come to the brink of physical destruction. And therefore, to harmonize the relations of the "human-nature" system with the aim of preserving the biosphere, the research of new forms of interaction of the "human-society", and "society-nature" systems at the global and regional levels is primarily important. Discussion. At first, ecology develops within the framework of biology, but gradually it goes beyond it and becomes the basis for the development of dozens of interdisciplinary sciences. The reason for the emergence of a wide range of environmental sciences is the awareness of an ecological threat to the future of humanity. Accordingly, solving such a global environmental problem is possible only with the joint efforts of specialists from all fields. A professional ecological discourse is gradually being formed, which in modern society has its own specificity and reveals unprecedented opportunities for the dissemination of ecological knowledge, the formation of ecological consciousness, and ecological culture at a qualitatively new level. Conclusion. Studying the dynamics and regularities of the development of the field of ecological knowledge and modern ecological discourse will reveal the shortcomings in current approaches to the development of environmental education and the formation of ecological culture.